Coordination under loss contracts - Steffen Ahrens; Lea Bitter; Ciril Bosch-Rosa (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
In this paper we study the effects that loss contracts - prepayments that can be clawbacked later - have on group coordination when there is strategic uncertainty. We compare the choices made by experimental subjects in a minimum effort game. In control sessions, incentives are formulated as a classic gain contract, while in treatment sessions, incentives are framed as an isomorphic loss contract. Our results show that loss contracts reduce the minimum efforts of groups and worsen coordination between group members, both leading to lower payoffs. However, these results depend strongly on the group's gender composition; groups with a larger proportion of women are better at coordinating and exert more effort.
Keywords: C91; D84; G11; G41; 330; strategic uncertainty; loss aversion; coordination; contract design; framing; experiment